Information Educational Environment of a Technical Higher Educational Institution - A. Gorovenko, Lyubov; P. Olkhovik, Oksana; V. Pavrozin, Alexander; V. Stadnik, Sergey (International Journal of Engineering and Technology, 2018)
Society periodically faces the requirement of high-quality changes of educational system, the educational environment. The problem of higher educational institutions includes intensive updating of the educational environment, tools, educational technologies and integration of infrastructure. System approach is necessary for development of the educational environment of a higher educational institution. For society on knowledge not only observance of requirements of educational standards, but also motivation of the identity of the student to professional self-development are important matters. Researchers try to consider environment conditions (evolutionary potential) and conditions of students (motivation). Self-development of the technical specialist â€“ a part of his professional activity, a way of independence in professional community in this activity. Self-development â€“ activity of the person in disclosure of personal potential. Information and the educational environment of a technical higher educational institution form directly knowledge, personal qualities of the student.In this article the system analysis of a problem of creation, structure, contents and updating of information and the educational environment of a technical higher educational institution is made. It is considered that the environment is innovative, stimulates pedagogical qualities. She unites educational resources and tools, technologies of management of educational process. In a technical higher educational institution a creative component of training - the corresponding part of training. Creative, competent technical specialists are required for society. Society wants to use the personified adaptive strategy of support of creative activity. The system analysis of a situation, the description of some methods of development of infrastructure of a technical higher educational institution and also the choice of strategy of self-training of the student are made in article. In her both strategic, and tactical targets of the technical higher educational institution participating in development of electronic economy are considered.Decisions which have to provide, in particular, development scientific and methodical, information and communication resources of infrastructure of a technical higher educational institution in situational modeling are provided. Some applied decisions are described.Â